1995
DOI: 10.1063/1.871405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular processes on the hydrogen atomic system in an expanding argon–hydrogen plasma

Abstract: . (1995). Influence of molecular processes on the hydrogen atomic system in an expanding argon-hydrogen plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In Fig. 2 14 it was reported that the Ar + ion density drops to an undetectable level with the inclusion of more than 4% H 2 . Those measurements, however, were performed at a distance of 20 mm from the arc.…”
Section: Resultsmentioning
confidence: 95%
“…In Fig. 2 14 it was reported that the Ar + ion density drops to an undetectable level with the inclusion of more than 4% H 2 . Those measurements, however, were performed at a distance of 20 mm from the arc.…”
Section: Resultsmentioning
confidence: 95%
“…This reaction is followed by dissociative recombination of the molecular-ion formed, 4 which is a very fast process with a rate of around 10 Ϫ13 m 3 s Ϫ1 at 3000 K. 18 When H 2 is added in the arc, argon ions are quenched by molecular hydrogen 23-28 with a rate of approximately 10 Ϫ15 m 3 s Ϫ1 . [23][24][25][26][27][28] This reaction is also followed by the very fast ͑approximately 10 Ϫ13 m 3 s Ϫ1 ͒ ͑Refs. 23-28͒ dissociative recombination of the formed ArH ϩ .…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…21,36 Therefore, we assume a uniform velocity for the flow of around 600-1000 m/s, 23,27,28 depending on the initial composition of the mixture. 37 The initial and final ͑i.e., at the substrate͒ ion flux have been measured by Kessels et al 3 and the velocity in the model is fitted so that the fluence calculated at the substrate position matches these values.…”
Section: Modelmentioning
confidence: 99%
“…However, the authors give an estimate for the downstream value of T e (about 0.4 eV) only in the case of a pure He plasma, based mainly on an analysis of highly excited He state populations. This spectroscopic method may give a reasonable estimate for n e in the case of a purely noble gas plasma, but only if careful and absolute calibration of the spectroscopy setup and tomographic reconstruction of the line-averaged data are performed [4,5]. Estimation of T e is then possible under specific equilibrium conditions.…”
mentioning
confidence: 99%
“…Actually, a T e determination by spectroscopic means may become impossible in this case, because (as OETKP indicate) the He I emission apparently disappears almost completely. To complicate things, the proposed molecular recombination mechanisms can strongly influence the excited state population [1,5] either directly or through influence on n e and T e . However, OETKP apparently just assume that the T e value does not change when going from the pure He plasma to the hydrogen puffing case and use the same value for this crucial parameter in the model simulations for the two cases.…”
mentioning
confidence: 99%